Preconception Counseling and Care in the Setting of HIV: Clinical Characteristics and Comorbidities - Rupsa C. Boelig; Jenell S. Coleman; Jean Keller; Catherine Sewell; Jean Anderson (Hindawi Limited, 2015)
Objective. To describe the demographic and clinical characteristics of HIV-infected individuals and HIV-affected couples who were referred for preconception counseling (PCC) at a large urban US-based HIV clinic. Methods. Electronic medical records were reviewed for HIV-infected individuals and HIV-affected couples. Medical, reproductive, surgical, psychosocial, and family history data were abstracted. Univariate analyses were done. Results. There were 8 single HIV-infected women and 100 HIV-affected couples who underwent PCC. HIV-infected women were older (mean age 35 years versus 32 years, P=0.06), were more likely to smoke (23% versus 0%, P<0.01), and had more medical comorbidities (57% versus 33%, P=0.04) than HIV-uninfected women. The majority of couples were serodiscordant (77%), and of these couples, 32% had a detectable plasma viral load and 33% report inconsistent condom use. Conclusions. HIV-infected women have a number of medical and psychosocial issues, including those related to HIV that may increase the risk of adverse pregnancy outcomes and HIV perinatal and sexual transmission. PCC is an important intervention to optimize maternal management to improve perinatal outcomes and minimize transmission risks.